2021
DOI: 10.3390/insects12050410
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Suggests the Introduction of Honeybees of African Ancestry to East-Central Europe

Abstract: In Europe, protecting the genetic diversity of Apis mellifera is usually perceived in the context of limiting the spread of the evolutionary C-lineage within the original range of the M-lineage. However, due to climate change and large-scale ongoing movement of breeding individuals, the expansion of bees from the African A-lineage could represent another threat. This issue has not yet been investigated in detail, although A-mitotypes occur in South-West and South Europe due to natural gene flow. Here, we deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 96 publications
2
25
1
Order By: Relevance
“…Approximately five worker bees from the apiary were chosen for genetic analysis, each representing one beehive. A total of 1696 sequences from neighbouring countries and Serbia originating from different time periods and deposited in NCBI GenBank [12,24,33,36,39,41,[44][45][46][47][48][49] were used for comparison (Table S2).…”
Section: Samplingmentioning
confidence: 99%
“…Approximately five worker bees from the apiary were chosen for genetic analysis, each representing one beehive. A total of 1696 sequences from neighbouring countries and Serbia originating from different time periods and deposited in NCBI GenBank [12,24,33,36,39,41,[44][45][46][47][48][49] were used for comparison (Table S2).…”
Section: Samplingmentioning
confidence: 99%
“…Using eDNA from honey samples can easily provide a more comprehensive sampling of honey bee DNA, with cost-effective possibilities to retrieve molecular information, as in our case, where mitotype information was easily discriminated. As far as we know, all of the previous studies that monitored A. mellifera mtDNA lineage distribution over broad geographical areas analyzed single honey bees, usually collected from different colonies (e.g., [ 1 , 2 , 4 , 5 , 43 , 58 , 59 , 60 ]). This approach gave the possibility to obtain more complete information of the mitotypes, but, on the other hand, could not include, in many cases, a very large number of colonies that would be needed to assure an optimal and detailed territorial representation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar explanations of the unexpected occurrence of the A lineage have been proposed by some authors, who reported African mtDNA lineages in other European countries. For example, Oleska et al [ 60 ] recently reported that about 2% of the honey bee colonies in East-Central Europe had A mitotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this legislation, the introduction of non-native bees is under state control. Despite conservation efforts, in recent years, the illegal introduction of non-native honey bees could have occurred, as in other European countries [56].…”
Section: Introductionmentioning
confidence: 99%